PENGEMBANGAN TUTS BOARD BERBANTUAN VIDEO TUTORIAL SEBAGAI MEDIA PEMBELAJARAN PIANIKA PADA KEGIATAN EKSTRAKURIKULER DI SMP NEGERI 29 PADANG - Shalsa Sabila, Shalsa Sabila; Alrizka Hairi Dilfa (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aimed to develop Tuts Board assisted by video tutorials as a learning medium for melodica instruction in extracurricular activities at SMP Negeri 29 Padang. The development of this learning medium was motivated by field observations showing that students still experienced difficulties in recognizing note positions on the melodica keys, understanding fingering techniques, and reviewing learning materials independently outside scheduled practice sessions. Therefore, a learning medium was needed to help students understand the material more concretely, systematically, and in an accessible manner. This study employed a Research and Development (R&D) method. The stages of the study included field observation, preliminary study, media design, product development, validation, revision, and limited trials. The Tuts Board media was designed using the Canva application, while the video tutorials were produced using the CapCut application. The research instruments consisted of material validation sheets, media validation sheets, and student practicality questionnaires. The data were analyzed using descriptive quantitative techniques through mean score calculation. The results showed that the Tuts Board assisted by video tutorials was categorized as valid and practical. Material validation obtained an average score of 4.75, media validation obtained an average score of 4.79, and the student practicality test obtained an average score of 4.74. These findings indicate that the developed media is feasible to be used as an alternative learning medium for melodica instruction in extracurricular activities at SMP Negeri 29 Padang.